Efforts to Improve the Performance of Bhabinkamtibmas in Preventing the Crime of Theft with Weights in the Pasuruan Police Jurisdiction Area - Syarifuddin, Muhammad Rafadhil Rizal (Police Studies Review, 2024)
This final assignment aims to analyze the performance of Bhabinkamtibmas in preventing criminal acts of theft with weights in the jurisdiction of the Pasuruan Police. The author uses a qualitative descriptive method and collects data through interviews, observations and documentation studies at the Urban Police and Rural Police within the jurisdiction of the Pasuruan Police. This final assignment covers three main issues, namely the management process, the strengths and weaknesses of Bhabinkamtibmas, and the performance itself. The management process includes planning, organizing, implementing and monitoring. Advantages and weaknesses include strengths, weaknesses, opportunities and challenges. Meanwhile, performance includes the number of members, quality of members, punctuality, attendance and ability to work together. In this final assignment, the author found that there were several inhibiting factors such as the absence of special planning, limited personnel both in terms of quality, the budget received was not optimal, and external obstacles and challenges such as the lack of public legal awareness, as well as perpetrators of criminal acts that are difficult to predict. From the results of this analysis, it is concluded that problem solving steps are needed to optimize the performance of Bhabinkamtibmas by improving the factors that influence the management process and its performance. Therefore, to strive to improve the performance of Bhabinkamtibmas, the author recommends several efforts, namely making plans regarding prevention, improving the quality of personnel, and increasing the budget, in order to maximize the performance of Bhabinkamtibmas. In this way, Bhabinkamtibmas can carry out its duties and responsibilities optimally as the person in charge of pre-emptive responsibility in the jurisdiction of the Pasuruan Police.